The Role of Celebrity Endorsement Perception and Self-Image Congruity on Purchase Intention of Early adulthood - N. Kardinah; Tintin Supriyatin; Khairunnisak Khairunnisak (Psympathic : Jurnal Ilmiah Psikologi, 2023)
Early adulthood is a transitional period towards the next developmental phase. During this period, students are subjected a process of self-discovery, characterized by a desire to appear more attractive and gain recognition from social environment. In such circumstances, individuals demonstrate a significant inclination to prioritize the allocation of financial resources away from meals and towards the purchase of items to amplify their attractiveness, recognition, and acceptance. This behavior is driven by the aspiration to align their ideal and actual self-image with the acquired products. Therefore, this study aimed to examine the influence of celebrity endorsement perception and self-image congruity on purchase intention. A quantitative approach was adopted with a sample of 344 students. The results of multiple linear regression analysis showed that celebrity endorsement perception and self-image congruity significantly influenced purchase intention, accounting for 58% of the variance.